STRENGTHENING THE REGULATORY FRAMEWORK AND SUPERVISION CONCEPT OF NOTARIES BY THE NOTARY SUPERVISORY COUNCIL IN BANKING ACTIVITIES IN INDONESIA: STRENGTHENING THE REGULATORY FRAMEWORK AND SUPERVISION CONCEPT OF NOTARIES BY THE NOTARY SUPERVISORY COUNCIL IN BANKING ACTIVITIES IN INDONESIA - Nurhadi, Dedi; Surono, Agus; Hamid, Adnan; Suasoongnern, Sineenart (PENA LAW: International Journal of Law, 2025)
Currently, the presence of a Notary is also required in the banking sector, where a Notary holds a central professional role by assisting both debtors and creditors in the preparation of principal agreements as well as collateral (accessory) agreements. Banks engaged in lending activities need the services of a Notary. The Notary profession is essential for institutions or companies acting as debtors in the process of obtaining bank credit. To fulfill their duties in the banking sector, Notaries must possess expertise and knowledge in the field of banking. Nowadays, Notaries are frequently found to be working in cooperation with banks or acting as bank partners, with such arrangements formalized in specific agreements. Notaries are often requested to draft credit agreements, in which most clauses are determined by the bank. The legal basis for the responsibilities carried out by a Notary is Article 16 paragraph (1) letter (a) of the Indonesian Law on Notary Office (UUJN), which requires a Notary to act with integrity, honesty, thoroughness, independence, impartiality, and to safeguard the interests of all parties involved in the legal act. A Notary’s independence must align with the principle of legal legality, so that in carrying out their duties, they are not influenced by any party or provide legal document services that favor one party over another. A Notary must uphold the principle of transparency, conduct examinations in accordance with the Notary Law and the Code of Ethics of the profession, and maintain independence and accountability for all information they provide. A potential issue faced by Notaries in the banking sector is the risk of a conflict of interest: on one hand, they must remain independent in performing their functions for the bank, while on the other hand, they receive professional fees from their clients and are bound to fulfill their professional responsibilities. Although Notaries are required to comply with the professional code of ethics and standards established by their professional association—and these must not contradict the Banking Law or its implementing regulations—the role and position of Notaries in banking require supervision by the Notary Supervisory Council. This is to ensure accountability in the Notary’s duties, as their actions may otherwise disadvantage the debtor or result in the preparation of incomplete or flawed deeds. Therefore, transparency in a Notary’s performance has become a matter of concern.